Analisis Pemenuhan Unsur Kesengajaan (Opzet) dalam Tindak Pidana Pembunuhan (Studi Putusan Nomor 1/Pid.Sus-Anak/2020/PN KPN) - Belicia Widhyana Yulia Putri; Adhari, Ade (UNES Law Review, 2024)
A criminal act is something committed by an individual who deliberately violates the provisions of the Criminal Code Book II Chapter XIX (Articles 338 to Article 350) due to the loss of someone's life. One example of this case is the murder incident in Decision Number 1/Pid.Sus-Anak/2020/PN KPN. In this case, there was a child who murdered the victim with the motive of self-defense, because the victim asked for the perpetrator's belongings and had sex with the witness. The perpetrator was subject to a sentence based on Article 351 paragraph (3) of the Criminal Code regarding abuse resulting in death by the Panel of Judges. However, this caused a polemic because the perpetrator committed the murder by stabbing a knife into the victim's vital organs in the chest. The author uses a normative juridical approach to examine the judge's views regarding the fulfillment of the element of intent (opzet) in the crime of murder using secondary data obtained through literature study. Based on the research results, the judge's consideration of the use of Article 351 paragraph (3) of the Criminal Code in this decision was considered inappropriate because the judge simply did not review the jurisprudence, the opzet element in this incident, and only relied on the Criminal Code and subjective reasoning. In criminal law, it is important to consider the element of intent or opzet, even though the consequences are the same, namely the loss of the victim's life, the element of intent in each article is different. Article 338 of the Criminal Code requires the victim to lose their life, while Article 351 paragraph (3) of the Criminal Code only wants the victim to feel pain without wanting the victim to die.